Multiscale correlated analysis of the Aguas Zarcas CM chondrite. (23rd March 2022) - Dionnet, Zélia; Aléon‐Toppani, Alice; Brunetto, Rosario; Rubino, Stefano; Suttle, Martin D.; Lantz, Cateline; Avdellidou, Chrysa; Baklouti, Donia; Borondics, Ferenc; Djouadi, Zahia; Grieco, Francesco; Héripré, Eva; et al.
Abstract: In this paper, we report the results of a campaign of measurements on four fragments of the CM Aguas Zarcas (AZ) meteorite, combining X‐ray computed tomography analysis and Fourier‐transform infrared (FT‐IR) spectroscopy. We estimated a petrologic type for our sampled CM lithology using the two independent techniques, and obtained a type CM2.5, in agreement with previous estimations. By comparing the Si‐O 10‐µm signature of the AZ average FT‐IR spectra with other well‐studied CMs, we place AZ in the context of aqueous alteration of CM parent bodies. Morphological characterization reveals that AZ has heterogeneous distribution of pores and a global porosity of 4.5 ± 0.5 vol%. We show that chondrules have a porosity of 6.3 ± 1 vol%. This larger porosity could be inherited due to various processes such as temperature variation during the chondrule formation and shocks or dissolution during aqueous alteration. Finally, we observed a correlation between 3D distributions of organic matter and mineral at micrometric scales, revealing a link between the abundance of organic matter and the presence of hydrated minerals. This supports the idea that aqueous alteration in AZ's parent body played a major role in the evolution of the organic matter.